Nano-advancements: Leveraging CoCuMnOx and CuO in solar stills for sustainable water solutions - Hebatullah Megahed; Nahed El Mahallawy (Next Materials)
Single-basin solar stills (SBSS) offer a promising solution, utilizing solar energy for water purification, particularly in remote and off-grid areas. The focus in the current study revolves around enhancing the performance of SBSS by introducing nanofluids, specifically CoCuMnOx and CuO nanoparticles (NPs). The main goal is to assess the impact of these NPs on the evaporation rate. CoCuMnOx NPs, synthesized via the sol-gel method, were characterized using SEM/EDX, XRD, FTIR, and UV spectroscopy, revealing a particle size of 500 nm and a solar absorbance of 88.35 %. Similarly, CuO NPs, with a particle size of 40 nm and solar absorbance of 91.14 %, were also investigated. Nanofluids with a 1 % volume fraction (Vf) of each NP type were prepared and subjected to evaporation rate testing. The experimental results indicated a significant increase in the evaporation rate by 65.33 % using CoCuMnOx nanofluids compared to distilled water, while CuO nanofluids showed a 33.24 % increase. Complementary to these experimental findings, numerical modeling predicts that the addition of 1 % Vf CuO nanofluid in SBSS with a cross sectional area 0.5 m² and under specific design and environmental conditions can achieve a cumulative productivity of 13 liters over an 8-h period. These findings highlight the potential for substantial performance enhancements through tailored material selection, nanofluid optimization, and system design. Overall, this research contributes to improving sustainable water desalination technologies with improved efficiency and effectiveness.